Hypocretin/orexin regulation of dopamine signaling: implications for reward and reinforcement mechanisms - España, Rodrigo; Calipari, Erin S. (Frontiers in Behavioral Neuroscience, 2012)
The hypocretins/orexins are comprised of two neuroexcitatory peptides that are synthesized exclusively within a circumscribed region of the lateral hypothalamus. These peptides project widely throughout the brain and interact with a variety of regions involved in the regulation of arousal-related processes including those associated with motivated behavior. The current review focuses on emerging evidence indicating that the hypocretins influence reward and reinforcement processing via actions on the mesolimbic dopamine system. We discuss contemporary perspectives of hypocretin regulation of mesolimbic dopamine signaling in both drug free and drug states, as well as hypocretin regulation of behavioral responses to drugs of abuse, particularly as it relates to cocaine.